Elucidating the impact of low doses of nanoformulated benznidazole in acute experimental Chagas disease - Rial, Marcela S. (2017)
Fil: Fil: Rial, Marcela S. Ministerio de Salud. Administración Nacional de Laboratorios e Institutos de Salud (ANLIS) “Dr. Carlos G. Malbrán”. Instituto Nacional de Parasitología “Dr. Mario Fatala Chaben”; Argentina.